'Pedantick', 'polite', or 'vulgar'? a systematic analysis of eighteenth-century normative discourse on pronunciation in John Walker's dictionary (1791). (2nd January 2016) - Trapateau, Nicolas
Abstract: John Walker is the first English lexicographer to provide a 'critical' pronouncing dictionary (1791) interspersed with his own critical notes on pronunciation. This paper identifies the phonological phenomena, whether praised or stigmatised, which are the targets of Walker's qualifiers — for example, which syllable of the word vertigo should be stressed in order to sound 'polite' or 'vulgar' in the 1790s. Building on such data, the study elicits Walker's sociolinguistic representation of the norm and the authorities who formulate it among the linguistic population of his time. This systematic analysis of Walker's normative discourse on English pronunciation is based on a text-searchable electronic version of Walker's dictionary.